HUMAN DEFICIENCY IN THE AGRO-INDUSTRIAL COMPLEX OF THE REPUBLIC OF SAKHA (YAKUTIA): WAYS TO SOLVE THE PROBLEMS - K. Togonokhov (Publishing House of the State University of Management, 2018)
This article deals with the problem of the personnel supply of the agro-industrial complex of the Republic of Sakha (Yakutia), caused by low conditions and quality of life in rural areas. The conducted research made it possible to identify the main problems of the personnel deficit in the agro-industrial complex under the conditions of Russia’s innovative economy, and also to identify the main reasons that hamper the employment of young specialists in rural areas. Particular attention is paid to the problem of training, professional development and professional training of specialists in the field of agroindustrial complex. Recommendations are proposed for the elimination of the personnel shortage and the formation of competitive personnel in the agro-industrial complex.